2021
DOI: 10.1002/cre2.400
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a novel bioluminescence imaging technology for aiding the assessment of carious lesion activity status

Abstract: Objectives: Clinical validation of a bioluminescence imaging system (Cis) as measured by the level of agreement between clinician visual and tactile assessment of carious lesion presence and activity and the presence/absence of elevated luminescence on a tooth surface determined from intraoral image mapping. Materials and Methods:This was a regulatory clinical study designed in consultation with the FDA. The design was a prospective, five-investigator, nonrandomized, postapproval, clinical study utilizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…An active lesion is considered to have a greater likelihood of transition (progress, arrest or regress) than an inactive lesion. However, such changes can normally be observed longitudinally to be sure that the initial assessment was valid [9], such as how it was performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An active lesion is considered to have a greater likelihood of transition (progress, arrest or regress) than an inactive lesion. However, such changes can normally be observed longitudinally to be sure that the initial assessment was valid [9], such as how it was performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The recently introduced digital imaging system Calcivis was developed as a bioluminescent marker to illuminate the assessment of dental caries and dental erosion through its binding of calcium ions, known to be released during the process of demineralization. In vitro and clinical studies have already been performed on occlusal and smooth surfaces [6][7][8][9], showing the ability of the bioluminescence method to visualize active demineralization and enamel erosion. However, Drancourt et al [22] concluded in an in vitro study that it was difficult to confirm the ability of a bioluminescence-based camera and a fluorescence-based system for the activity assessment of coronal carious lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations